Trends of colorectal cancer incidence and mortality rates from 2003 to 2014 in Italy. Issue 5 (October 2019) - Zorzi, Manuel; Dal Maso, Luigino; Francisci, Silvia; Buzzoni, Carlotta; Rugge, Massimo; Guzzinati, Stefano
Objective: To evaluate the trends of colorectal cancer (CRC) incidence and mortality rates from 2003 to 2014 in Italy by age groups and regions. Methods: We used the data of 48 cancer registries from 17 Italian regions to estimate standardized incidence and mortality rates overall and by sex, age groups (<50, 50–69, 70+ years), and geographic area (northwest, northeast, center, south, and islands). Time trends were expressed as annual percent change in rates (APC) with 95% confidence intervals (95% CI). Results: Incidence rates decreased from 104.3 (2003) to 89.9 × 100, 000 (2014) in men and from 64.3 to 58.4 × 100, 000 in women. Among men, incidence decreased during 2007–2010 (APC −4.0, 95% CI −6.0 to −1.9) and 2010–2014 (APC −0.7, 95% CI −1.4 to 0.0), while in women it linearly decreased during the whole period (APC −1.1, 95% CI −1.4 to −0.8). Mortality rates showed a linear reduction both in men (APC −0.7, 95% CI −1.0 to −0.3) and women (APC −0.9, 95% CI −1.2 to −0.6) and decreased respectively from 41.1 to 39.2 × 100, 000 and from 24.6 to 23.1 × 100, 000. In the 50- to 69-year-old range (screening target age), incidence showed a prescreening increase, followed by a peak after screening started, and a decline thereafter. Incidence and mortality rates significantly decreased in all areas but in the south and islands, where incidence increased and mortality remained stable. Conclusions: A renewed commitment by all regional health systems to invest in primary (i.e., lifestyle) and secondary (i.e., screening programs) prevention is of utmost importance.